Adventures of Mary Jane - Jahren, Hope (Delacorte Press, 2024)
Before meeting Huckleberry Finn, Mary Jane faces deadly illness, treacherous landowners, and swindlers as she goes on her own thrilling journey down the Mississippi in pre-Civil War America.